KAJIAN HUKUM POLEMIK BLACKLIST BI PADA PROGRAM JAHE MERAH DI BANGKA TENGAH - Andrian, Doni; H. Farid Effendi; Virna Dewi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
The Red Ginger Program, which was initiated by Erzaldi Rosman Djohan, former Governor of Bangka Belitung, aims to empower the people of Central Bangka through the cultivation of red ginger by providing loans channeled through Bank Sumsel Babel. However, this program caused serious legal problems when around 400 residents involved in the program were blacklisted by Bank Indonesia (BI) due to crop failure and inability to pay off loans they considered as assistance. This creates legal uncertainty and limits citizens' access to financial services. This research uses normative juridical methods with a qualitative approach to examine legal issues arising from the provision of loans in the Red Ginger program and their impact on residents' credit status. Data was collected through interviews with affected residents, representatives of Bank Sumsel Babel, and analysis of related legal documents. The research results show that there is a mismatch between residents' expectations and the reality of program implementation, especially in terms of information dissemination and transparency. Many residents did not receive adequate explanation that the assistance was a loan that had to be repaid, thus having a negative impact on their credit record.This research reveals the need to increase socialization and transparency in the implementation of economic empowerment programs, as well as strict law enforcement to protect citizens' rights. In conclusion, a legal solution is needed that can ensure legal certainty and protect citizens' rights in future economic empowerment programs.